Physical activity levels in American and Japanese men from the ERA-JUMP Study and associations with metabolic syndrome - Naoko Sagawa; Bonny Rockette-Wagner; Koichiro Azuma; Hirotsugu Ueshima; Takashi Hisamatsu; Tomoko Takamiya; Aiman El-Saed; Katsuyuki Miura; Andrea Kriska; Akira Sekikawa (Elsevier, 2020)
Background: Metabolic syndrome (MetS) is a global health problem. Physical activity (PA) is a known modifiable risk factor for MetS and individual MetS components. However, the role of PA could differ between sub-populations due to differences in the variability of PA and other MetS risk factors. To examine these differences, multi-country studies with standardized outcome measurement methods across cohorts are needed. Methods: Cross-sectional PA levels (total and domain specific) in healthy middle-aged (44-56 years) men in the Risk Factor Assessment among Japanese and U.S. Men in the Post-World War II Birth Cohort (ERA-JUMP) Study (n = 730; American: n = 417; Japanese: n = 313; from population-representative samples in Pittsburgh, Pennsylvania, USA, and Kusatsu, Shiga, Japan) were compared. The relationships between PA levels and MetS (overall and specific components) in/across the American and Japanese sub-cohorts (adjusting for age, smoking, and alcohol consumption) were also assessed using the same instruments (pedometer and validated questionnaire) to measure PA in both cohorts. Results: A total of 510 individuals provided complete data on PA (American: n = 265; Japanese: n = 245). The American cohort had significantly lower mean ± SD steps/day (7878 ± 3399 steps/day) vs. the Japanese cohort (9055 ± 3797 steps/day) (p < 0.001) but had significantly higher self-reported moderate-vigorous leisure PA (American: 15.9 (7.4-30.3) metabolic task equivalent hours per week (MET-h/week) vs. Japanese: 4.0 (0-11.3) MET-h/week, p < 0.0001). In both sub-cohorts, each 1000 steps/day increase was associated with lower odds of having MetS (American: OR = 0.90, 95%CI: 0.83-0.98; Japanese: OR = 0.87, 95%CI: 0.79-0.95) and the individual MetS component of high waist circumference (American: OR = 0.86, 95%CI: 0.79-0.94; Japanese: OR = 0.87, 95%CI: 0.80-0.95). In the American cohort only, higher self-reported leisure PA (Met-h/week) was associated with lower odds of MetS and high waist circumference (OR = 0.98, 95%CI: 0.97-0.99 for MetS and waist circumference, respectively). Conclusion: Higher total step counts/day had an important protective effect on MetS prevalence in both the Japanese and American cohorts, despite differences in PA levels and other MetS risk factors. The effect of steps/day (across all intensity levels) was much greater than domain-specific moderate-vigorous PA captured by questionnaire, suggesting the need for measurement tools that can best capture total movement when examining the effects of PA on MetS development. Keywords: Epidemiology, Metabolic syndrome, Pedometer, Physical activity, Questionnaire